2013
DOI: 10.1007/s12031-013-0122-5
|View full text |Cite
|
Sign up to set email alerts
|

Nutri-epigenetics Ameliorates Blood–Brain Barrier Damage and Neurodegeneration in Hyperhomocysteinemia: Role of Folic Acid

Abstract: Epigenetic mechanisms underlying nutrition (nutrition epigenetics) are important in understanding human health. Nutritional supplements, for example folic acid, a cofactor in one-carbon metabolism, regulate epigenetic alterations and may play an important role in the maintenance of neuronal integrity. Folic acid also ameliorates hyperhomocysteinemia, which is a consequence of elevated levels of homocysteine. Hyperhomocysteinemia induces oxidative stress that may epigenetically mediate cerebrovascular remodelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 39 publications
(44 reference statements)
2
73
0
Order By: Relevance
“…GM6001 is a broad-spectrum MMP inhibitor and has been previously tested for various cerebral pathologies; for example, intracerebral hemorrhage [26], altered cellular migration [27], and BBB permeability [28]. MMPs are one of the main culprits involved in cerebral disease progression and we and others have reported that MMP-9, a gelatinase, is associated with impairment of the neurovasculature function, hemorrhagic transformations, neurodegeneration, and BBB disruption [15, 17, 29, 30]. In this current report, we established that attenuating MMP-9 using a synthetic inhibitor, GM6001 rescued hypertension-induced vasculopathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GM6001 is a broad-spectrum MMP inhibitor and has been previously tested for various cerebral pathologies; for example, intracerebral hemorrhage [26], altered cellular migration [27], and BBB permeability [28]. MMPs are one of the main culprits involved in cerebral disease progression and we and others have reported that MMP-9, a gelatinase, is associated with impairment of the neurovasculature function, hemorrhagic transformations, neurodegeneration, and BBB disruption [15, 17, 29, 30]. In this current report, we established that attenuating MMP-9 using a synthetic inhibitor, GM6001 rescued hypertension-induced vasculopathy.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are expressed in various cell types, including ECs, and are involved in various functions such as; subendothelial matrix (SEM) degradation, extracellular matrix (ECM) and vascular remodeling [15, 16]. We have previously shown the involvement of MMP-9 in cerebrovascular dysfunction [17, 18], by degrading the cerebral vasculature. Our lab including others clearly showed that MMP-9 attenuation can ameliorate cerebral pathologies [15, 1820].…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting study showed that the supplement of folate could improve Hcy-induced bloodebrain barrier damage and neurodegeneration in hyperhomocysteinemia mouse, which had the heterozygous CBS mutation [22]. According to the previous epidemiological study in Tao, the prevalence of psychotic symptoms is much higher than Han Taiwanese population (Tao tribe: 1.6%, Han Taiwanese: 0.3%) [23].…”
Section: Discussionmentioning
confidence: 99%
“…Hyperhomocysteinemia is known to cause an imbalance between MMPs and TIMPs leading to the accumulation of collagen. Kalani et al [26] showed that a rise in the protein/mRNA expression of MMP-2 and MMP-9 and a drop in the mRNA expression of TIMP-1 and TIMP-2 were observed in the brain tissues of cystathionine-beta-synthase heterozygote knockout methionine-fed mice. Bescond et al [27] found that low molar ratio of Hcy enhanced the activity of MMP-2.…”
Section: Discussionmentioning
confidence: 99%